A Survey: Dual watermarking Techniques using 2 DWT, DCT & SVD - Somra, D.S; Gupta, M (International Journal of Computer Sciences and Engineering, 2018)
Digital image watermarking (DIW)is the way toward embedding watermark into a digital image (DI) for validation and in this way protecting the DI from copyright encroachment. In this paper, a versatile undetectable watermarking plan is proposed in dual watermarking process. It is expected that the simplicity with which advanced media can be replicated will prompt an expansion of copyright encroachment.. The implement work calculation is depicted in subtle elements. The calculation has 2 strategies; the watermark installing strategy and the watermark extraction systems. This zone gives two changes used as a piece of the proposed computation to watermark government report pictures. The 2 changes are the 2 level DWT and SVD. The 2 transform and dual watermarking are useful in course in such an approach to misuse their appealing properties.